High-pressure oxygen rewires glucose metabolism of patient-derived glioblastoma cells and fuels inflammasome response. (28th May 2021) - Arienti, Chiara; Pignatta, Sara; Zanoni, Michele; Zamagni, Alice; Cortesi, Michela; Sarnelli, Anna; Romeo, Antonino; Arpa, Donatella; Longobardi, Pasquale; Bartolini, Daniela; Tosatto, Luigino; Naldini, Antonella; et al.
Abstract: Human glioblastoma (GBM) is one of the most feared primary malignant brain tumors. We investigated the effect of hyperbaric oxygen (HBO) on GBM patient-derived cells and on microglia cell biology (CHME-5). HBO administered to GBM cells inhibited cell proliferation, downregulated hypoxia-inducible factor 1 α (HIF-1α) expression, and induced glucose metabolism reprogramming (glucose rewiring). It also affected the ability of a cell to perpetuate its lineage, give rise to differentiated cells and interact with its environment to maintain a balance between quiescence, proliferation and regeneration (stemness features). Such an effect may be ascribable to an increase in intracellular ROS levels and to the triggering of inflammasome signaling by HBO itself through caspase1 activation. Moreover, the results obtained from the combination of HBO and radiotherapy (RT) clearly showed a radiosensitising effect of HBO on GBM cells grown in both 2D and 3D, and a radioprotective effect of HBO in CHME-5. In addition, the exposure of M0 microglia cells to exhausted medium or extracellular vesicles (EVs) of HBO-treated GBM cells upregulated the expression of pro-inflammatory cytokines IL1β, IL6 and STAT1, whilst also downregulating the anti-inflammatory cytokine PPARγ. Collectively, these data provide a scientific rationale for the use of HBO in combination with RT for the treatment of patients with GBM. Graphical abstract: Image 1 Highlights: HBO, inhibited glioma cell proliferation and down-regulated the expression of HIF-1. HBO rewired the glucose metabolism and affected stemness features. HBO and RT showed a radiosensitising effect of HBO on GBM patient derived cells. HBO and RT showed a radioprotective effect on microglia cells. HBO acts on the cross-talk between glioma cells and microglia.